If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23x = x Solving 23x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 23x + -1x = x + -1x Combine like terms: 23x + -1x = 22x 22x = x + -1x Combine like terms: x + -1x = 0 22x = 0 Divide each side by '22'. x = 0 Simplifying x = 0
| 20y+20=70 | | 20y+10=80 | | sin(2z+i)=2cos(2z+i) | | 64+64+64+64+64+64+64+64+64= | | ex=1 | | 48m-28m+12m= | | (x-2)+1+3x=5(x+1) | | 16x^2+24x+9=6 | | 12x+12=5x+96 | | 79-5x=13x+21 | | 5(x+1)-6x=3x-9 | | c-5c+7c= | | cos(x)+2x=0 | | 4x-1×(0.5)3-2x=1/8-x | | x*x+2x-23.333=0 | | 12+9x=6x | | 0.65=0.3+0.7x | | 5(x/6-x/2)-7(x/2-x/4)=9 | | 5(x/6-x/2)-80 | | x:2x+9=6 | | 30(a*a*a)*2(a*a*a*a)=1 | | (5x+3y)=360 | | 3xsquare+x-5=0 | | 4x-20=3x+8 | | 67x-4*9=0 | | (6-2x)/(6x-x^2)=0 | | mx+m=x^2+2mx+1 | | x^2+mx+1-m=0 | | -16x^3+x^2+16=0 | | z^11/7z^2 | | 3g+5d= | | 3g+5d=1 |